2019
DOI: 10.1016/j.cgh.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Rates of and Factors Associated With Placebo Response in Trials of Pharmacotherapies for Nonalcoholic Steatohepatitis: Systematic Review and Meta-analysis

Abstract: In a meta-analysis of randomized controlled trials of NASH, patients given placebo have significant histologic, radiologic, and biochemical responses. The placebo response should be considered in designing trials of agents for treatment of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 140 publications
(46 reference statements)
4
91
2
2
Order By: Relevance
“…While this was only a single‐arm pilot study, the positive results and low dropout rates suggest that this concept can be successfully implemented for the benefit of a patient with NAFLD. Previous meta‐analysis of placebo groups from randomised controlled trials in NASH highlighted that a placebo response can lead to reductions in BMI, transaminases and other surrogate parameters of liver injury . Albeit the absence of a control group in the current study, post hoc analysis of patients that failed to complete the predefined threshold of 70% of exercise sessions, did not show any beneficial effects.…”
Section: Discussioncontrasting
confidence: 54%
“…While this was only a single‐arm pilot study, the positive results and low dropout rates suggest that this concept can be successfully implemented for the benefit of a patient with NAFLD. Previous meta‐analysis of placebo groups from randomised controlled trials in NASH highlighted that a placebo response can lead to reductions in BMI, transaminases and other surrogate parameters of liver injury . Albeit the absence of a control group in the current study, post hoc analysis of patients that failed to complete the predefined threshold of 70% of exercise sessions, did not show any beneficial effects.…”
Section: Discussioncontrasting
confidence: 54%
“…The current study reports an effective longitudinal histological assessment of a 12‐week therapy. To reduce the risk of unnecessary exposure of patients in the placebo group to two biopsy procedures in short succession, we conducted open‐label enrollment with a central read on slides blinded to time points and compared our results to historical placebo responses from a meta‐analysis of 39 randomized controlled trials comprising 1,463 patients with NASH . A greater proportion of patients treated with NGM282 3 mg compared with historical placebo control had improvement in fibrosis (42% versus 21%), steatosis (74% versus 33%), hepatocellular ballooning (53% versus 30%), and lobular inflammation (42% versus 32%).…”
Section: Discussionmentioning
confidence: 99%
“…According to recently published systematic reviews, histologic outcomes have been reported in 37 randomised, placebo‐controlled trials of adult patients with NASH (Table S1). Of these trials, 30 used the NAS system for assessing disease activity and fibrosis.…”
Section: Methodsmentioning
confidence: 99%